Impact of uterine fibroids on fertility and pregnancy: a study of modern approaches to infertility treatment - Nuriddinova Madina (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
Amidst the global rise in infertility, uterine fibroids remain one of the most significant factors negatively impacting female reproductive function. The study aims to provide a comprehensive assessment of the pathology's impact on fertility and a comparative analysis of modern treatments for associated infertility. The practical significance of the work lies in substantiating approaches that promote the restoration of reproductive health and improve gestational outcomes.